Air Quality Index Levels of Particulate Matter (PM2.5) in Yenogua, Nigeria - Francis Olawale Abulude; Kikelomo Mabinuola Arifalo; Amoke Monisola Kenni; Akinyinka Akinnusotu; Samuel Dare Oluwagbayide; Acha Sunday (Jurnal Pendidikan Geografi Gea, 2022)
Air pollution is a worldwide issue that is receiving attention. The rationale for this is the threat to human health. PM2.5 has been attributed to human mortality, morbidity, asthma, chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, cancer, type 2 diabetes, neurodegenerative diseases, obesity, and a variety of other ailments, according to research. Because of the accessibility of indoor and outdoor environmental quality documents in advanced nations, the problems are being mitigated, whereas little has been achieved in developing countries due to an insufficiency of records. The findings of this study could be used to close this gap while also assisting policymakers in Nigeria. In this work, the 11-day Air Quality Index (AQI) of Yenagoa, Bayelsa State was obtained using satellite-based data provided by IQAir. The results are shown as: AQI (46-80), PM2.5 (11.1-26.2 µg/m3), temperature (24-31 oC), speed (3.3-12.5 m/s), and relative humidity (RH) (60-91 %). The data clearly showed that the majority of the PM2.5 concentrations were below the World Health Organization (WHO) guideline of 25 µg/m3 daily. The levels of concern for AQI affirmed that air quality ranged between good and moderate, suggesting that the area's air quality is satisfactory with little or no risk.